2017
DOI: 10.12669/pjms.336.13489
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Celiac disease in Paediatric population: Experience of Tertiary Care Center from Pakistan

Abstract: Objective:To determine clinical features and relevant laboratory investigations of patient with celiac disease (CD) and comparing classical celiac disease (CCD) with Non-diarrheal celiac disease (NDCD).Methods:This is a five years retrospective study conducted at The Aga Khan University Hospital Karachi, Pakistan from January 2010 to December 2015, enrolling children from one year to 15 years of either gender diagnosed as celiac disease in accordance with revised ESPGHAN criteria. Biopsy samples with grade 2 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
3
2
0
Order By: Relevance
“…Marsh 3b and advance stage were more commonly present in classic celiac disease as compare to non-classic variety, in which early grade was more common. This is in accordance with multiple studies that show a high grade of histopathological findings in patients with gastrointestinal symptoms [ 13 ]. Although villous atrophy is the hallmark of CD.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Marsh 3b and advance stage were more commonly present in classic celiac disease as compare to non-classic variety, in which early grade was more common. This is in accordance with multiple studies that show a high grade of histopathological findings in patients with gastrointestinal symptoms [ 13 ]. Although villous atrophy is the hallmark of CD.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, 30% of NCCD presented with short stature only. This is quite similar to the study performed by Aziz et al [ 13 ]. Therefore many studies recommend screening for CD in severely short stature.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In a study by Aziz DA et al on 66 children with classic and non-classic CD found that only 2 (3.03%) had autoimmune thyroiditis. 12 However, the studies conducted by Meloni A et al and Kalyoncu D et al found higher percentage of AT (10.5%) among 324 patients with CD and 16.4% (11/67) of children with CD, respectively. 13 , 14 The high risk of CD patients to develop AT is explained by the fact that the Celiac disorder carries one or more MHC or other immune related genes supporting AT.…”
Section: Discussionmentioning
confidence: 92%